Predictors of benefit from an atopic dermatitis education programme - Breuer, Kristine; Matterne, Uwe; Diepgen, Thomas L.; Fartasch, Manigé; Gieler, Uwe; Kupfer, Jörg; Lob‐Corzilius, Thomas; Ring, Johannes; Scheewe, Sibylle; Scheidt, Reginald; Schmid‐Ott, Gerhard; Schnopp, Christina; et al. (Pediatric allergy and immunology, 2014)
Background Multidisciplinary, age-related, structured, group educational programmes for children with atopic dermatitis (AD) and their parents have shown positive long-term outcomes with respect to quality of life and coping behaviour of the participants. We aimed to identify predictors of favourable long-term outcome of an education measure for parents of children with AD aged 3 months to 7 years in the framework of The German Atopic Dermatitis Intervention Study (GADIS). Methods In an exploratory approach, the data of 274 child-parent pairs were analysed with respect to the influence of various somatic and psychological variables as possible predictors of treatment success. Changes in parents' QoL, SCORAD (Scoring Atopic Dermatitis), topical corticosteroid use and parents' knowledge about AD between baseline and 12-months' follow-up were chosen as measures of long-term treatment success (outcome). Results Psychological rather than somatic parameters were identified as predictors of treatment success. Parents who had negative treatment experiences in the past and possessed only poor coping abilities with regard to scratch control benefitted the most from the training programme. The outcome of the education measure was independent of parents' schooling, vocational level and income. Conclusions Parents of children with AD who lack adequate coping abilities should be particularly encouraged to take part in such an education programme.
Gesehen am 31.08.2020